Leaching of metals from soil contaminated by mining activities - (:unkn) unknown (ELSEVIER, 2001)
Stabilization/solidification (s/s) is one of the most effective methods of dealing with heavy metal contaminated sites. The ability of lime and cement stabilization to immobilize Pb, Cu and Fe contained in a contaminated soil originating from an old mining and smelting area located along the Mediterranean Sea shore in northern Cyprus was investigated. The stabilization was evaluated by applying leaching tests. A series of tests were conducted to optimize the additive soil ratio for the best immobilization process. Additive/soil = 1/15 (m/m) ratio was found to be the optimum for both lime and cement. Application of the US EPA toxicity characteristic leaching procedure (TCLP) on the soil samples treated with lime at additive/soil = 1/15 (m/m) mixing ratios showed that Cu and Fe solubility was reduced at 94 and 90%, respectively. The results of cement treatment using the same ratio, reduced the solubility 48 and 71% for Cu and Fe, respectively. The Pb solubility was found to be below the regulatory limit of 5 mg/l so no additive treatment was needed. The optimum additive/soil amount (1/15) was selected for more detailed column studies, that were carried out in the acidic pH range. According to the results of column leaching tests, it was found that, the degree of heavy metal leaching is highly dependent on pH. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: remediation; mining activity; lead; copper; stabilization/immobilization; SOLIDIFICATION; WASTES